On the calculation of volume. III - Balle, Solvej, 1962- (New Directions paperbook, 2025)
"Tara's November 18th transforms when she discovers that she is no longer alone in her endless autumnal day. For she has met someone who remembers, and who knows as well as she does that 'it is autumn, but that we're not heading into winter. That spring and summer will not follow. That the reds and yellows of the trees are here to stay. That yesterday doesn't mean the seventeenth of November, that tomorrow means the eighteenth, and that the nineteenth is a day we may never see.' Where Book I and II focused on a single woman's involuntary journey away from her life and her loved ones and into the chasm of time, Book III brings us back into the realm of companionship, with all its thrills, odd quirks, and a sense of mutual bewilderment at having to relearn how to exist alongside others in a shared reality. And then of course, what of Tara's husband Thomas, still sitting alone day after day, entirely unawares, in their house in Clarion-sous-Bois, waiting for his wife to return? Blending poetry and philosophical inquiry with rich reflections on our discombobulating times, Balle's On the Calculation of Volume asks us to consider: What is a single person's responsibility to humanity and to the preservation of this world?"--